Micro‐Supercapacitors: Highly Stretchable Micro‐Supercapacitor Arrays with Hybrid MWCNT/PANI Electrodes (Adv. Mater. Technol. 3/2017). Issue 3 (March 2017) - Li, La; Lou, Zheng; Han, Wei; Chen, Di; Jiang, Kai; Shen, Guozhen
Abstract : In article number 1600282, Wei Han, Guozhen Shen, and co‐workers describe the fabrication of stretchable micro‐supercapacitors exhibiting a large areal capacitance and an excellent mechanical stability/flexibility by hybrid multiwalled carbon nanotube (MWCNT)/polyaniline (PANI) electrodes, showing potential applications in skin‐patchable electronics or portable/wearable devices.